Modelling of non-premixed turbulent combustion of hydrogen using conditional moment closure method - M. M., Noor; A. Aziz, Hairuddin; Wandel, Andrew P.; Yusaf, T. F. (IOP Publishing, 2012)
Most of the electricity generation and energy for transport is still generated by the conversion of chemical to mechanical energy by burning the fuels in the combustion chamber. Regulation for pollution and the demand for more fuel economy had driven worldwide researcher to focus on combustion efficiency. In order to reduce experimental cost, accurate modelling and simulation is very critical step. Taylor series expansion was utilised to reduce the error term for the discretization. FORTRAN code was used to execute the discretized partial differential equation. Hydrogen combustion was simulated using Conditional Moment Closure (CMC) model. Combustion of hydrogen with oxygen was successfully simulated and reported in this paper.